236 Optimizing Haploidentical Donor Selection for Pediatric Hematopoietic Cell Transplant. (April 2022) - Liberio, Nicole; Shaw, Bronwen; Yanik, Greg; Qayed, Muna; Schultz, Kirk; Broglie, Larisa
Abstract : OBJECTIVES/GOALS: Patients who require a hematopoietic cell transplant (HCT) and dont have an HLA-matched related or unrelated donor may rely on a haploidentical donor. The optimal haploidentical donor and guidance for selection is limited. We aim to determine how donor characteristics affect outcomes following haploidentical-HCT for pediatric patients. METHODS/STUDY POPULATION: This is a retrospective cohort study evaluating the effect of donor age and relationship on post-HCT outcomes in children (0-18y) from 2008-2018. Multivariable logistic regression analysis will identify if donor age or donor relationship affect the development of graft-versus-host-disease (GVHD), while adjusting for other patient, donor, and transplant related variables. Two-year overall survival & event-free survival will be determined using Kaplan-Meier curves, stratified by donor age group and donor relationship, and compared by log-rank testing. Sub-analyses will be performed for myeloablative transplants and reduced intensity conditioning, as well as for malignant and non-malignant diseases. RESULTS/ANTICIPATED RESULTS: Our primary aim to is determine the effect of donor age and the effect of donor relationship to patient on the development of GVHD. We hypothesize that utilization of a younger donor will decrease the incidence of GVHD. Further, we hypothesize that utilizing a sibling haploidentical donor will result in less GVHD than a parental donor. Secondary aims include evaluating the effect of donor age and donor relationship on overall survival, event-free survival, non-relapse mortality, relapse, graft failure and time to engraftment. The results of this study will help us to develop criteria for optimal haploidentical donor selection. If donor selection is optimized, this could result in improved outcomes following haploidentical transplants. DISCUSSION/SIGNIFICANCE: Haploidentical donors are increasingly used as many patients, especially ethnic minorities, do not have an HLA-matched donor. This will be the largest study of haploidentical HCT in children. The data gathered will allow us to identify important donor characteristics to help guide physician decision-making when choosing a haploidentical donor.